2020
DOI: 10.1007/s10980-020-00998-7
|View full text |Cite|
|
Sign up to set email alerts
|

Coupling landscape graph modeling and biological data: a review

Abstract: ContextLandscape graphs are widely used to model networks of habitat patches. As they require little input data, they are particularly suitable for supporting conservation decisions (and decisions about other issues as e.g. disease spread) taken by land planners. However, it may be problematic to use these methods in operational contexts without validating them with empirical data on species or communities. ObjectivesSince little is known about methodological alternatives for coupling landscape graphs with bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…Whatever the type of landscape graph used, the impact of the temporal dynamics of connectivity on biodiversity can be either assumed or tested. This dichotomy is found in all studies of connectivity using landscape graphs (Foltête et al 2020). The first set of studies investigates the temporal dynamics of connectivity without testing their effects on biodiversity.…”
Section: Theoretical Background: Graph Theorymentioning
confidence: 99%
“…Whatever the type of landscape graph used, the impact of the temporal dynamics of connectivity on biodiversity can be either assumed or tested. This dichotomy is found in all studies of connectivity using landscape graphs (Foltête et al 2020). The first set of studies investigates the temporal dynamics of connectivity without testing their effects on biodiversity.…”
Section: Theoretical Background: Graph Theorymentioning
confidence: 99%
“…Finally, models based on graph theory provide interesting leads to implement biodiversity offsets by contributing to preserving biodiversity and the functionality of natural environments (Foltête, 2019). But we can note two major limitations: they are only based on the availability of spatially explicit data on species' habitat and their uncertainty is rarely assessed (Gippoliti and Battisti, 2017; but see Foltête et al, 2020). Therefore, even if our understanding of connectivity is improved by modelling approaches, we will still need to collect field data, on species behavior, habitat quality and demography (Kool et al, 2013).…”
Section: Recommendations To Stakeholdersmentioning
confidence: 99%
“…2018) used validation methods based on observed dispersal paths de ned from GPS locations to compare the output of connectivity approaches based on resistance surfaces estimated from presence-only data, telemetry and genetic data. However, in a review of the use of biological data in combination with landscape graphs, Foltête et al (2020) found that telemetry and molecular data represent only 8.4% of the studies and are much less used than presence data, that can be easily extracted from existing databases, especially in studies with operational objectives. Therefore, further validation procedures are required.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further validation procedures are required. Foltête et al (2020) found few papers that used biological data (regardless of data type) both a priori and a posteriori while the classical statistical procedure of validation consists in calibrating a model with a subsample of data and validating it with another subsample (Fielding and Bell, 1997). The a priori use of biological data informs landscape connectivity approaches of species requirements (e.g.…”
Section: Introductionmentioning
confidence: 99%